1986
DOI: 10.1002/j.2048-7940.1986.tb00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Arousal and Fear in the Spinal Cord Injured

Abstract: A quasi‐experimental design was used to test the relationship between neurological status (cervical complete spinal cord injury versus lower thoracic‐lumbar spinal cord injury versus no injury — 15 subjects each group), physiological arousal, and self‐reports of fear in subjects exposed to a fear‐inducing film segment. Partial support was obtained for the hypothesis that neurological status is related to physiological arousal. Non‐injured subjects displayed the greatest arousal, with significant increases in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…41 It was based on our hypothesis that the amount of spinal cord tissue "lost to the brain" was a paramount factor in determining potential neurocognitive differences among our study groups. 41 It was based on our hypothesis that the amount of spinal cord tissue "lost to the brain" was a paramount factor in determining potential neurocognitive differences among our study groups.…”
Section: Resultsmentioning
confidence: 99%
“…41 It was based on our hypothesis that the amount of spinal cord tissue "lost to the brain" was a paramount factor in determining potential neurocognitive differences among our study groups. 41 It was based on our hypothesis that the amount of spinal cord tissue "lost to the brain" was a paramount factor in determining potential neurocognitive differences among our study groups.…”
Section: Resultsmentioning
confidence: 99%
“…Blood pressure (BP), pulse (P), and galvanic skin response (GSR) were used as autonomic response variables. As other nursing investigators have shown (Anderson, 1989;Carr, 1990;Winters, 1986), it is often useful to include objective measures as confirmatory data for more subjective indicators such as qualitative response or self report. This was the intention in employing autonomic measures of arousal in conjunction with the FSS-III.…”
Section: Methodsmentioning
confidence: 99%